Regulation of glucose uptake in mammalian cells by protein phosphorylation - Henriques, Andreia (2018)
Cancer cells demand increased amounts of glucose to sustain their proliferation and upregulate plasma membrane expression of glucose transporter GLUT1. In insulin responsive cells, glucose uptake requires previous phosphorylation of TBC1D4, a negative regulator of endosomal GLUT traffic. Previous work published by the host lab has discovered that protein kinase WNK1 can also phosphorylate TBC1D4 and promote the translocation of GLUT1 to the cell surface.